FOOD PREFERENCE OF CALLOSOBRUCHUS MACULATUS (F.) TO SIX TYPES OF GRAINS OF FABACEAE - SUNITA P. ZANKE; HITAL C.LOLGE; SURESHCHANDRA ZAMBARE (The Bioscan, 2015)
Dry pulses,rich sources of proteins for good health, are highly infested by several stored grain pests. The food preferences of pulse beetle, Callosobruchus maculatus (F.) on six types of pulses studied under laboratory conditions showed 5% attractions in Cajanus cajan (red gram),7.14 % in Lens esculenta (lentils), 27.6 % in Phaseolus mungo (blackgram), 31.9 % in Vigna catjung (cowpea),7.35 % in Cicer arietium (kalachana) and 9.25% in Vigna aconitifolia (matki). Vigna catjung (cow pea) and Phaseolus mungo (black gram) were most preferred food for this species while Cajanus cajun (red gram) was comparatively less preferred for oviposition and further growth. Highest mean number of eggs were deposited on Vigna catjung (61.56), while in Cajanus cajan least number of eggs were deposited (10.09). Eggs deposited on Lens esculenta (lentils) were 15.57, on Phaseolus mungo (blackgram) were 50.09, on Cicer arietium (kalachana) were 20.09 while in Vigna aconitifolia (matki) were 25.75. Vigna catjung (cow pea) and Phaseolus mungo (black gram) were most preferred food and for oviposition and hence are suitable to prepare baits.